The alkynylphosphonate analogue of calcitriol EM1 has potent anti-metastatic effects in breast cancer - Ferronato, María Julia (2015)
The active form of vitamin D3, calcitriol, plays a major role in maintaining calcium/phosphate homeostasis. In addition, it is a potent antiproliferative and prodifferentiating agent. However, when effective antitumor doses of calcitriol are employed, hypercalcemic effects are observed, thus precluding its therapeutic application. To overcome this problem, structural analogues have been designed with the aim at retaining or even increasing the antitumor effects while decreasing its calcemic activity. This report shows the biological evaluation of an alkynylphosphonate vitamin D less-calcemic analogue in amurine model of breast cancer. We demonstrate that this compound has potent anti-metastatic effects through its action over cellular migration and invasion likely mediated through the up-regulation of Ecadherin expression. Based on the current in vitro and in vivo results, EM1 is a promising candidate as atherapeutic agent in breast cancer.